Idea korelacji Nieba i ludzkości jako paradygmat religii konfucjańskiej - Rogacz, Dawid (Przegla̜d religioznawczy, 2017)
In this article, I would like to reconstruct the basic assumption of the Confucian religion, which came to life in the 2nd c. B.C., i.e. the idea of the correlation of Heaven and humankind (Tiān-rén gǎnyìng 天人感應). To that end, I will examine the writings of Dong Zhongshu and other selected Han Dynasty thinkers. I will try to show that although Confucianism of that time did not assume any transcendent being or salvation, it fulfills the criteria of the religious phenomenon.